?Using Poetry in EFL Classes: Is It an Effective Learning Tool or It Is a Kind of Redundancy - Khadija Ali Alhibshi (المجلة الأفروآسيوية للبحث العلمي, 2025)
This study investigates the effectiveness of using poetry as a pedagogical tool in EFL Libyan classroom at English department, Faculty of Education, Elmergib University. The study focuses specifically on learners' perceptions and previous experiences during poetry course to identify the role of poetry in learning language from students' perspectives. The researcher adopted qualitative approach and used semi-structured, face-to-face interviews for collecting required data that analyzed inductively. The participants of the study were ten female students enrolled in third year, (2024-2025). The findings revealed that poetry is an effective tool for learning language. Students felt that they were motivated, and their language developed in pronunciation, vocabulary, oral skills, cognitive skills and their emotional awareness increased. In short, poetry is a powerful pedagogical tool and it has an educational function which provides an environment where poetry and linguistics complement each other.